Vesicoureteral Reflux and Duplex Systems - John C. Thomas (Advances in Urology)
Vesicoureteral reflux (VUR) is the most common anomaly associated with duplex systems. In addition to an uncomplicated duplex system, reflux can also be secondary in the presence of an ectopic ureterocele with duplex systems. Controversy exists in regard to the initial and most definitive management of these anomalies when they coexist. This paper will highlight what is currently known about duplex systems and VUR, and will attempt to provide evidence supporting the various surgical approaches to an ectopic ureterocele and duplex system and the implications of concomitant VUR.